(untitled) (Hoboken, N.J., 2003)
Corporate Aftershock is a reasoned, informed response to the numerous proposals to restrict derivatives, structured financing activities, and shareholder protection principles and practices following the failure of Enron and other corporations. Readers get a cogent analysis of the public policy world after recent corporate debacles. Corporate Aftershock provides a detailed background of the markets, players, regulations, and institutional environment surrounding these failures.
Keywords: Disclosure in accounting,Corporations,Industrial policy; Accounting